First report of the lesser wax moth Achroia grisella F. (Lepidoptera: Pyralidae) consuming polyethylene (silo-bag) in northwestern Argentina - Chalup, Adriana Elizabeth (2018)
In this note, we report the lesser wax moth Achroia grisella F. (Lepidoptera: Pyralidae) (LWM), a beehive pest, for the first time in Argentina. In addition, we report observations of the larvae of this pest species consuming “silo-bags,” a material commonly used in the country for hive management. Silo-bags are composed of three layers of polyethylene and one anti-UV layer and no records of insects consuming this material are found in the literature. Our report represents a warning for apiculture in Argentina, especially when honey production has been observed to decrease recently. This decrease may be a result of a combination of factors, which may include the poor monitoring of hive health, and inappropriate management of pests such as A. grisella. In addition, our observations on silo-bag consumption represent a call for attention to beekeepers that use this material to conserve heat in the hives and open questions about the mechanisms involved in silo-bag consumption by the larvae.